Umbrella Cells Mimicking Focal High-Grade Urothelial Carcinoma in Low-Grade Papillary Urothelial Carcinoma. (11th September 2019) - Hassan, Muhammad Masood; Naab, Tammey; Afsari, Ali
Abstract: Objectives: Low-grade papillary urothelial carcinoma (LGUC) has overall a preserved orderly appearance, minimal variability in architecture, and lack of significant cytologic atypia and mitotic activity without pleomorphism. A total of 53.8% of LGUC cases recur with 18.3% progression to high-grade UC. Even focal HGUC in LGUC can be a harbinger of progression. Accurate pathological interpretation is paramount in predicting recurrence and determining treatment. Methods: A 63-year-old male with a past medical history of coronary artery disease, benign prostate hyperplasia, and obesity was referred to urology with a chief complaint of chronic hematuria. Cystoscopy with transurethral resection of bladder tumor was performed, which revealed mainly LGUC with focal high-grade-appearing UC. Results: Histologic sections revealed papillary architecture with fused fronds, low-grade nuclear atypia, and scattered mitoses comprising 95% of the tissue submitted. No muscular wall invasion by carcinoma was seen. However, in one section, collections of large cells with well-defined cytoplasmic borders, multinucleation, and rare nuclear grooves were identified. The morphology raised the suspicion of a focal HGUC. Diffuse expression of CK20 and low Ki-67 proliferation index (1%) favored umbrella cells. Conclusion: Our case reinforces the fact that sectioning can reveal foci, suspicious for HGUC, especially in urothelium. However, proper interpretation of morphology combined with the help of immunohistochemistry aids in accurate diagnosis, which is critical in determining proper clinical management of the patient.